2003
DOI: 10.1093/humrep/deg260
|View full text |Cite
|
Sign up to set email alerts
|

Testicular sperm extraction (TESE) and ICSI in patients with permanent azoospermia after chemotherapy

Abstract: Some patients with permanent azoospermia after chemotherapy can be successfully treated by TESE-ICSI. This procedure, however, may have potential genetic risks. Therefore, freezing semen before starting gonadotoxic therapy is the strategy of choice, and patients should be counselled accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 50 publications
4
58
1
15
Order By: Relevance
“…There are many studies investigating SRR and results of ICSI in patients with NOA (Kahraman et al, 1996b;Meseguer et al, 2003). Parameters affecting spermatozoa retrieval and success of surgical technique have also been examined (Turunc et al, 2010;Ghalayini et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies investigating SRR and results of ICSI in patients with NOA (Kahraman et al, 1996b;Meseguer et al, 2003). Parameters affecting spermatozoa retrieval and success of surgical technique have also been examined (Turunc et al, 2010;Ghalayini et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In humans and primates where spermatozoa may be isolated in testicular biopsies, it has been shown that recovery after severe damage occurs only focally in a few seminiferous tubules. Patients will be permanently infertile if tubules become fully hyalinized or a complete Sertoli cell only pattern is established (32,33). The spermatogenic stem cells are susceptible to this type of damaging insult at all ages, but the full impact on spermatogenesis manifests itself during onset of puberty (34).…”
Section: Differences In Germline Stem Cell Biology In Females and Malmentioning
confidence: 99%
“…All pubertal boys with testis volumes above 10 -12 mL are encouraged to donate a semen sample before cancer therapy (43,44). Alternatively, electro-ejaculation or testicular sperm extraction from a biopsy can be used as a source to retrieve spermatozoa for boys unable to ejaculate (33). Expediency in fertility preservation due to urgency for immediate cancer therapy poses a unique issue in these young patients (see discussion on ethical aspects below).…”
Section: Cryopreservation Of Gametesmentioning
confidence: 99%
“…Fertilitenin geri dönebilmesi için bu hücrelerin belirli bir süre sonra yeniden A (koyu) tip hücrelerden oluşması gerekmektedir. Daha yüksek dozlarda A (koyu) spermatogonia hücreleri de hasar görüp hastada kalıcı azoospermiye ve seminifer tubuller içerisinde sadece Sertoli hücrelerinin bulunduğu yapının oluşmasına neden olabilir (26,27). Uygulanan doz dışında fertilitenin korunmasında kullanılan kemoterapötik ajan, radyasyon uygulamalarında uygulanan bölge, uygulama sıklığı da rol oynamaktadır (28).…”
Section: Radyoterapi Ve Kemoterapinin Fertilite üZerinde Etkisiunclassified